Analisis Kestabilan dan Bifurkasi pada Model Matematika Penyebaran Penyakit Meningitis dengan Perlakuan Vaksinasi dan Pengobatan - Rabiatul Adawiyah; Syamsuddin Toaha; Kasbawati Kasbawati (Jurnal Matematika, Statistika dan Komputasi, 2022)
Meningitis is an infectious disease that occurs in inflammation of the meninges and the spinal cord in consequence of bacteria and viruses. Vaccination and treatment using antibiotics is used to increase growth rate in infected people so that the spread rate can be reduced. This study aims to see the effect of vaccination and treatment using some compartments:  susceptible, carrier, infected without symptoms, infected with symptoms, recovery without disability, and recovery with disability; show the sensitivity analysis in order to discover the parameter that affect basic reproduction number and bifurcations analysis. The result from sensitivity found the relation between parameter and  that can increase and decrease the  value. This study also showed the influence of stability change from equilibrium point caused by the parameter  value change form bifurcations analysis. Models simulation show that the effect of vaccination and treatmen for spread of meningitis can be handled.